2011
DOI: 10.1345/aph.1p605
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin Complex Concentrate Versus Standard Therapies for INR Reversal in Trauma Patients Receiving Warfarin

Abstract: PCC, when added to FFP and vitamin K, resulted in a more rapid time to reversal of the INR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 22 publications
3
44
1
Order By: Relevance
“…[18][19][20][21] Conclusions that can be drawn from these studies are limited, however, because of their observational nature and the lack of standardization of the time after PCC administration until measurement of the INR. In most studies of three-factor PCC for warfarin reversal, PCC was used in addition to FFP, which could reduce FFP dosing requirements.…”
Section: Urgent Warfarin Reversalmentioning
confidence: 99%
“…[18][19][20][21] Conclusions that can be drawn from these studies are limited, however, because of their observational nature and the lack of standardization of the time after PCC administration until measurement of the INR. In most studies of three-factor PCC for warfarin reversal, PCC was used in addition to FFP, which could reduce FFP dosing requirements.…”
Section: Urgent Warfarin Reversalmentioning
confidence: 99%
“…[26][27][28][29] of PCC for warfarin reversal. Six studies [22][23][24][26][27][28] specifically assessed the efficacy of PCC in traumatic or spontaneous intracranial hemorrhage, whereas 2 studies [25,29] focused on reversal of supratherapeutic INR. Boulis and colleagues [22] was an open-label randomized trial conducted at a single institution that compared the time and rate of warfarin reversal in patients with traumatic intracranial bleeding who were treated with 3-factor PCCs or FFP.…”
Section: Reversal Of Warfarin Anticoagulationmentioning
confidence: 99%
“…The retrospective studies comparing PCC to matched historical controls [26][27][28][29] demonstrated reduced subsequent intracerebral hematoma expansion [26,27]-albeit without major improvements in function-as well as quicker achievement of INR target [27][28][29]. Safety outcomes were not reported in 2 studies [26,27].…”
Section: Efficacy and Safety Outcomes In Reversal Of Warfarin Anticoamentioning
confidence: 99%
“…The results of one retrospective analysis demonstrated that in trauma patients receiving warfarin, the addition of PCC treatment to FFP and vitamin K treatment yielded a more rapid INR reversal; however, no clear improvement in clinical outcomes was noted [51].…”
Section: Traumamentioning
confidence: 99%